MOLECULAR DIAGNOSIS OF MARINE BIRNAVIRUS IN THE ZOOPLANKTON FROM VELLAR ESTUARY (SOUTH EAST COAST OF INDIA) - C.RAJTHILAK,; P.PERUMAL,; A. MURUGAN,; S.S.JAYARAJ,; P.SANTHANAM, (International Journal of Pharma and Bio Sciences, 2010)
Marine birnavirus (MBVs) infect a wide range of fish and shellfish. Yet their mode of transmission is still unclear. To determine marine plankton serve as a vector for MABVs. The marine birnavirus (MABVs) is a member of Aquabirnavirus and an opportunistic pathogenic form among eukaryotic marine organisms and determine the viral presence in zooplankton as a vector, molecular diagnosis can be used. The present investigation of Zooplankton Acartia and Oithona species were collected separately. They were diagnosed for the presence of viral genome by 2 step PCR method. The result was positive in both of them and this suggests that molecular diagnosis will help us to identify viral presence in the stock larvae before they are stocked in the rearing ponds. It will be certainly helpful for the farmers whose life dependent on the healthy culturing of fishes.